Ketamine and Active Ketamine Metabolites Regulate STAT3 and the Type I Interferon Pathway in Human Microglia: Molecular Mechanisms Linked to the Antidepressant Effects of Ketamine - Ho, Ming-Fen; Zhang, Cheng; Zhang, Lingxin; Li, Hu; Weinshilboum, Richard M. (Frontiers in Pharmacology, 2019)
Inflammation is an important biological process which contributes to risk for depression, in part as a result of the production of proinflammatory cytokines and of alterations in glutamatergic neurotransmission. Ketamine has anti-inflammatory properties which might contribute to its antidepressant effects. This study was designed to clarify mechanisms of action for ketamine and its active metabolites, (2R,6R;2S,6S)-hydroxynorketamine (HNK), which also appear to play a major role in ketamine’s rapid antidepressant effects. An HMC3 human microglial cell line was used as a model system to test a possible role for ketamine in immune response regulation that might contribute to its antidepressant effects. Our results highlight the fact that ketamine and its two active metabolites can regulate the type I interferon pathway mediated, at least partially, through STAT3 which plays a major role in the immune response. Specifically, STAT3 downstream genes that were modulated by either ketamine or its active metabolites were enriched in the “response to type I interferon” pathway. Our data also suggest that STAT3 might play a role in ketamine’s antidepressant effects, mediated, at least in part, through EEF2, resulting in the augmentation of BDNF expression and promoting the synthesis of synaptic proteins PSD95 and SYN1.